2015
DOI: 10.5114/aoms.2015.53306
|View full text |Cite
|
Sign up to set email alerts
|

Basic research Suppression of human hepatocellular cancer cell proliferation by Brucea javanica oil-loaded liposomes via induction of apoptosis

Abstract: IntroductionHepatocellular carcinoma (HCC) is a type of malignancy with high incidence and poor prognosis. Brucea javanica is extracted from Simaroubaceae plants. It is found to have low toxicity but high anti-cancer efficiency. The aim of this study is to determine the effects of Brucea javanica oil-loaded liposomes (BJOL) on human hepatocellular cancer cell line HepG2. The related molecular mechanisms were determined.Material and methodsMorphologic changes of HepG2 cells were observed by transmission electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Currently, sorafenib, which blocks tumor cell proliferation and angiogenesis, is the only treatment recommended for advanced HCC on the basis of 2 phase III clinical trials [ 19 , 20 ], although another substance, Brucea javanica extract, has been found to inhibit cell proliferation and increase apoptosis in animal and cellular studies of HCC [ 30 ]. It prolongs survival in advanced HCC patients by about 3 months [ 19 , 20 ] and is equally effective in younger and older (> 75 years) patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, sorafenib, which blocks tumor cell proliferation and angiogenesis, is the only treatment recommended for advanced HCC on the basis of 2 phase III clinical trials [ 19 , 20 ], although another substance, Brucea javanica extract, has been found to inhibit cell proliferation and increase apoptosis in animal and cellular studies of HCC [ 30 ]. It prolongs survival in advanced HCC patients by about 3 months [ 19 , 20 ] and is equally effective in younger and older (> 75 years) patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the control group, the in vivo treatment group of Brucea javanica (L.) Merr extracts had lower metastasis rate and higher body weight. The Brucea javanica (L.) Merr extracts induce apoptosis in hepatocellular carcinoma tissue in a dose-dependent manner [ 176 ].…”
Section: Recent Research On the Roles Of Herbs And Phytochemicals mentioning
confidence: 99%
“…Previous studies show that the BJOE combination therapy could promote liver cancer cell apoptosis by regulating the expression of soluble Fas/soluble Fas ligand [ 28 ] and BJOE also induces apoptosis in the colon cancer cells [ 28 ]. Another study finds that BJO-loaded liposomes inhibits the proliferation of hepatocellular cancer HepG2 cells, which appears be dose-dependent, possibly by inducing apoptosis of cancer cells [ 31 ]. However, in our study, the BJOE combination seemed to have the same DCR rate (odds ratio = 1.04, p = 0.663) compared with chemotherapeutic agents alone.…”
Section: Discussionmentioning
confidence: 99%